2004
DOI: 10.1103/physrevd.70.034029
|View full text |Cite
|
Sign up to set email alerts
|

Accessing the longitudinally polarized photon content of the proton

Abstract: We investigate the QED Compton process in longitudinally polarized lepton-proton scattering both in the elastic and inelastic channels and show that the cross section can be expressed in terms of the polarized equivalent photon distribution of the proton. We provide the necessary kinematical constraints to extract the polarized photon content of the proton using this process at HERMES, COMPASS, and eRHIC. We also discuss the suppression of the major background process coming from virtual Compton scattering. We… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In fact, a significant photon content of the proton is well confirmed in the so-called Deep Inelastic Compton Scattering (DICS, see Refs. [21][22][23][24][25][26] and Fig. 3).…”
Section: Light Sea Fermionsmentioning
confidence: 87%
“…In fact, a significant photon content of the proton is well confirmed in the so-called Deep Inelastic Compton Scattering (DICS, see Refs. [21][22][23][24][25][26] and Fig. 3).…”
Section: Light Sea Fermionsmentioning
confidence: 87%
“…At HERA energies, σ EPA inel = 3.64 × 10 −2 pb, 3.51 × 10 −2 pb and 3.07 × 10 −2 pb for Q 2 max =ŝ, −û and −t, respectively. In the following we will fix the scale to beŝ, in analogy to our previous studies about the QED Compton scattering process in ep → eγX [2,4,5]. In [4,5] it was suggested that the experimental selection of only those events for whichŝ > Q 2 restricts the kinematics of the process to the region of validity of the EPA and improves the extraction the equivalent photon distribution from the exact cross section.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…The polarized and unpolarized photon distributions of the nucleon, evaluated in the EPA, have been computed theoretically [1] and the possibility of their experimental determination has also been demonstrated [2,3,4,5]. Both of them consist of two components, an elastic one, due to N → γN, and an inelastic one, due to N → γX, with X = N. The reliability of the EPA remains, however, to be studied.…”
Section: Introductionmentioning
confidence: 99%